تأثير الوسائط المتعددة على تعزيز مهارات حل المشكلات الرياضية ودافعية الإنجاز في الرياضيات بين طلاب الصف السابع في مقاطعة شمال الشرقية بسلطنة عمان - جابري، إسحاق حميد سعيد (Kulliyah of Education, International Islamic University Malaysia, 2021)
This study aims to focus on some points : the effect of multimedia in reinforcing the problem-solving skills to overcome mathematical issues. It aims to measure students motivation and achievement in mathematics in grade 7 in North Sharqiyah Governorate as well as knowing statistically significant differences between the control and experiential groups, and the pre and post scale. Moreover, the study targets to raise the most important suggestions from teachers and specialists in developing the programmes of multimedia. The study is meant to get answers about different questions which the researcher raised to achieve the aims required. In addition, the researcher used the descriptive approach and the quasi-experimental method on a sample of students in the North Sharqiyah Governorate, numbering ( 153 students ) of the class of the seventh-grade students in the basic stage for mathematics and the study included some tools to do the achievement test in the skills of solving mathematical problems before and after the control and experimental group, as well as the measure of motivation in mathematics, and the sample was divided into a control group (77 students) and an experimental group (76 students), and the results appeared: There is a statistically significant difference between the mean scores of the pre and post measurements for the students of the experimental group that studied according to the multimedia program on the test of solving mathematical problems for the mathematics course as well as the measure of motivation in mathematics for the benefit of the post group. There is a statistically significant difference at the level of significance between the mean scores of the experimental group students and the control group students on the test of solving mathematical problems as well as the measure of motivation in mathematics for the benefit of the experimental group. The researcher used (Make It) application to implement the study. The study recommended popularizing the idea and increasing reliance on e-learning, as well as recommending more studies in this field and researching the impact of multimedia and educational electronic games on the development of intelligence in children